Eleanor the Great [videorecording (DVD)] - Kamen, Tory; Squibb, June, 1929-; Kellyman, Erin; Hecht, Jessica, 1965-; Zohar, Rita; Ejiofor, Chiwetel; O'Halloran, Dustin, 1971-; Broecker, Tom; Louvart, Hélène (Sony Pictures Home Entertainment, 2025)
After seventy years with her best friend, Eleanor suffers a devastating loss and moves to New York City for a fresh start. Making new friends at ninety proves difficult. Longing for connection, she befriends a 19-year-old student.